2021
DOI: 10.1002/bit.27965
|View full text |Cite
|
Sign up to set email alerts
|

Outer membrane vesicles (OMVs) enabled bio‐applications: A critical review

Abstract: Outer membrane vesicles (OMVs) are nanoscale spherical vesicles released from Gram-negative bacteria. The lipid bilayer membrane structure of OMVs consists of similar components as bacterial membrane and thus has attracted more and more attention in exploiting OMVs' bio-applications. Although the endotoxic lipopolysaccharide on natural OMVs may impose potential limits on their clinical applications, genetic modification can reduce their endotoxicity and decorate OMVs with multiple functional proteins. These ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 81 publications
0
19
0
Order By: Relevance
“…Compared with the scalable and chemically designable PVs, the use of OMVs in targeted drug delivery has only been sporadically reported in recent years and is still an emerging area requiring urgent research [ 28 ]. Sangyong Jon’s study is recognized as the first report on using OMVs for targeted drug delivery [ 55 ].…”
Section: Drug Delivery Performance Of Pvs and Omvsmentioning
confidence: 99%
“…Compared with the scalable and chemically designable PVs, the use of OMVs in targeted drug delivery has only been sporadically reported in recent years and is still an emerging area requiring urgent research [ 28 ]. Sangyong Jon’s study is recognized as the first report on using OMVs for targeted drug delivery [ 55 ].…”
Section: Drug Delivery Performance Of Pvs and Omvsmentioning
confidence: 99%
“…Outer membrane vesicles (OMVs) are spherical nanovesicles that are naturally released by gram-negative bacteria with a lipid bilayer and the size is approximately 20-250 nm [92,93]. In 1997, Bermudes and his colleagues found that Salmonella can be a novel drug delivery platform for targeting cancer [94].…”
Section: Bacterial Outer Membrane Vesicles In Cancer Immunotherapymentioning
confidence: 99%
“…The main function of EVs is the transport of various classes of macromolecules, including lipids, polysaccharides, proteins, and nucleic acids [ 9 , 16 , 19 ]. Through this cargo, these structures perform a number of key functions in microorganisms, including long-distance transport of nutrients, protection against environmental stressors, or communication during microorganism–microorganism or microorganism–host interactions [ 16 , 17 , 20 ]. The importance of EVs in the virulence of many live-threatening pathogens is well known and widely described in the literature [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%